Novel Echocardiography-Derived Left Ventricular Stiffness Index in Low-Flow Versus Normal-Flow Severe Aortic Stenosis with Preserved Left Ventricular Ejection Fraction - Ngiam, J.N. (Nature Research, 2021)
10.1038/s41598-020-65758-8